(untitled) (Our Nature, 2025)
This study shows the oxygen uptake rates of Tilapia (Oreochromis niloticus), in relation to body weight during two distinct seasonal temperature conditions: winter (20±1°C) and summer (30±1°C). The relationship between oxygen consumption (mlo2/hr) and body weight was analyzed using the equation y=a.Wb, where (a) is the intercept and (b) is the regression coefficient. In winter, the regression coefficient (b) was 0.7038, with a correlation coefficient (r) of 0.9972 (p<0.01), and the antilog of the intercept (a) was 0.375. Oxygen uptake rates varied inversely with weight, with values of 0.2898 (mlO2/g/hr), 0.1981(mlO2/g/hr), 0.1570 (mlO2/g/hr) for 2g, 9g, and 17g, respectively. During summer, the regression coefficient (b) increased to 0.8028, with a correlation coefficient (r) of 0.9937 (p<0.01) and the antilog of the intercept was 0.551. Oxygen uptake rates similarly decreased with weight, ranging from 0.5542 (mlO2/g/hr), 0.3374 (mlO2/g/hr), and 0.3230 (mlO2/g/hr) for 2g, 10g and 19g fish, respectively.